Prevalence of copepod parasite (Lernaeenicus polynemi) infestation on Eleutheronema tetradactylum from Pazhayar coastal waters, southeast coast of India - Bharadhirajan, Pazhanivel; Gopalakrishnan, Ayyaru; Raja, Kuzhanthaivel; Murugan, Sambantham; Vijayakumar, Ramalingam; Rahman, Mohammad Mustafizur (Coastal Life Medicine Media co., Limited, 2013)
Objective: To study the prevalence and mean intensity of copepod parasite Lernaeenicus polynemi infestation on Eleutheronema tetradactylum from Pazayar, Tamil Nadu, of India. southeast coast Methods: The fish was collected from Pazhayar landing centre from January to December 2012 aonf dp atrhaesiirt ebsi owmeeretr rice cmoredaesdu.rements were examined. Toal number of infected fish and total number. Results: Higher prevalence and mean intensity of infestation of 35.23% and 3.1 were respectively rbeopdoyr toefd t hdeu rhinosgt manodn stoaorgne steedas tohne odfi f2f0e1r2e.n Tt hinet epranraals iotircg ainnsfe ssutacthio anss lwiveerre asncda tttheree ddo orvsaelr athoret ae.n Ttihree highest intensity was reported to be 66 parasites in a single host. Conclusions: Due to the heavy parasitic attack the fish will suffer and its economical value or the marketability may reduce.